HUBUNGAN WAKTU ANTARKLAUSA YANG DIHUBUNGKAN DENGAN SETSUZOKUJOSHI TOKI - Rini, Elizabeth Ika Hesti Aprilia Nindia; Risagarniwa, Yuyu Yohana; Johana, Jonjon (Universitas Negeri Jakarta, 2012)
The main clausesituation that linked by setsuzokujoshitoki occured just before, simultaneously,or justafter thesubordinateclausesituation occur. However setsuzokujoshitoki impliesthat both of clauses areoccuredat the same time of range. Chronology of these clauses and the gramatical meaningof setsuzokujoshitokidetermined bysubordinateclause predicate’s typeand predicate’sform.